How Many Quechuan Languages Are There? An Estimation of the Number of Quechuan Languages - Camacho Rios, Gladys (2024)
If the practice of referring to a single “Quechua language” is incorrect because it does not acknowledge the many distinct “Quechuan languages” spoken in the Andean countries, then how many are there? In this study we propose an approximate number based on an application of the most relevant criteria for the distinction between languages/dialects to the Quechuanist literature: (1) degree of mutual intelligibility, (2) phonological-morphosyntactic similarity, (3) lexical correspondence, (4) sociolinguistic perspectives, and (5) geographic fragmentation. Adding up each region individually, we arrive at a total of approximately 12~17 languages. This result highlights the diversity of the Quechuan family as much for linguistics as for public and community policies, which would be more successful if instead of promoting standardization, they valued this diversity.